Política neoliberal no Brasil e sua implicação na estrutura de propriedade de empresas de capital aberto privatizadas - Cardoso, Alexandra Andrade de Almeida (2012)
The theme of this work focuses on the ownership structure of state enterprises and publicly traded, and it aims to analyze how the neoliberal, the developmental and the business logics dictaded a change in the ownership structure of state enterprises which were privatized in the period 1990 to 2007. In order to understand the changing structure conditioned by institutional logics, we developed a documentary research in primary sources that was collected, among others, in databases such as CVM, BOVESPA, and specific secondary in economic policy and business were searched in Valor Econômico newspaper and the magazine Traded and Examination, and also in books and also in specialized sites about the theme. The study shows that while the privatization process the institutional logics conditioned the change in ownership structure of state-owned publicly traded, the state continues to participate indirectly in the economy, mainly through BNDES and the Public Pension Funds.